Progressive Encephalopathy in Boys with Symptoms of Rett Syndrome and MECP2 Mutations - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
Four young boys with neonatal onset of encephalopathy, a progressive course, and MECP2 mutations are reported from the University of Alabama, Birmingham, AL Symptoms suggestive of Rett syndrome included failure to thrive, respiratory insufficiency, microcephaly, hypotonia, movement disorder, with myoclonic, dyskinetic, and choreiform patterns, and repetitive face scratching or nose rubbing stereotypies.